Fed up [videorecording (DVD)] - Brook, Michael, 1952- (Anchor Bay Entertainment, 2014)
Narrated by Katie Couric, the film blows the lid off everything that was known about food and exercise, revealing a 30-year campaign by the food industry, aided by the U.S. government, to mislead and confuse the American public. Exposing the hidden truths contributing to one of the largest health epidemics in history, it follows a group of families battling to lead healthier lives and reveals why the conventional wisdom of 'exercise and eat right' is not ringing true for millions of people.